2019
DOI: 10.1080/1359866x.2019.1576029
|View full text |Cite
|
Sign up to set email alerts
|

Do stereotypes strike twice? Giftedness and gender stereotypes in pre-service teachers’ beliefs about student characteristics in Australia

Abstract: Stereotypes influence teachers' perception of and behaviour towards students, thus shaping students' learning opportunities. The present study investigated how 315 Australian pre-service teachers' stereotypes about giftedness and gender are related to their perception of students' intellectual ability, adjustment, and social-emotional ability, using an experimental vignette approach and controlling for social desirability in pre-service teachers' responses. Repeated-measures ANOVA showed that pre-service teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 54 publications
2
31
0
12
Order By: Relevance
“…Sin embargo, también se aprecia una visión restringida sobre la AC, la cual pone mayor énfasis en el rendimiento, sin necesariamente considerar otros elementos propios de su expresión, como por ejemplo la creatividad. Por lo demás, algunas de las conceptualizaciones de los participantes sobre la AC están teñidas por aspectos socioemocionales negativos, tales como la presencia de conductas disruptivas en el aula (Al Zoubi, 2018;Matheis et al, 2019;Oswald & De Villiers, 2013). Dichas conductas tienden a opacar la percepción que tienen los directivos respecto de estos estudiantes, no necesariamente entendiéndolas como efectos de la desatención educativa a la cual están expuestos, si no como una característica propia de la AC.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Sin embargo, también se aprecia una visión restringida sobre la AC, la cual pone mayor énfasis en el rendimiento, sin necesariamente considerar otros elementos propios de su expresión, como por ejemplo la creatividad. Por lo demás, algunas de las conceptualizaciones de los participantes sobre la AC están teñidas por aspectos socioemocionales negativos, tales como la presencia de conductas disruptivas en el aula (Al Zoubi, 2018;Matheis et al, 2019;Oswald & De Villiers, 2013). Dichas conductas tienden a opacar la percepción que tienen los directivos respecto de estos estudiantes, no necesariamente entendiéndolas como efectos de la desatención educativa a la cual están expuestos, si no como una característica propia de la AC.…”
Section: Discussionunclassified
“…Por su parte, Matheis et al (2019), mencionan que los profesores asociaban la AC a estudiantes con una inteligencia superior, y a la vez los percibían con bajos niveles de ajuste conductual y social en comparación con sus pares no talentosos. Algunos hallazgos apuntan a la existencia de una serie de mitos y estereotipos predominantes, tales como que los estudiantes con AC no necesitan apoyos especiales y que lograrán el éxito por sí solos ( Hafenstein et al, 2017).…”
Section: Alta Capacidadunclassified
“…Teachers' perspectives appeared to be due to a range of factors including giftedness not being covered in initial teacher education and a lack of professional development for teachers related to giftedness within the Lebanese education system. Matheis et al (2019) also found limited teacher education affected teacher beliefs, self-efficacy about providing effective educational provision for gifted students. Plunkett and Kronborg found that professional learning for pre-service teachers (Plunkett & Kronborg, 2011; can significantly change teacher attitudes and beliefs about teaching gifted students with one semester of teaching and reading for assessment of evidence-based gifted education literature.…”
Section: Lack Of Awareness Of Appropriate Practices Used To Identify Gifted Studentsmentioning
confidence: 95%
“…An interwoven relationship is argued to exist between beliefs and attitudes, as a person's perceptions and attitudes are shaped by their beliefs (Ajzen, 2012;Maio & Haddock, 2010;Matheis et al, 2017;Matheis et al, 2019;Plunkett, 2000). Stern and Keislar (1975) maintain that teachers' construction of attitudes is acquired from cultural knowledge, which is based on their beliefs about their students, and includes a predisposition to perform or respond to particular situations in their classrooms.…”
Section: Importance Of Perceptions and Attitudesmentioning
confidence: 99%
“…Thus, the development of interest in STEM areas for women may be negatively influenced by the overlap of stereotypes regarding gender, HA, and scientists (e.g., male, lonely, working indoors, etc. ), as these students are socialised by parents and teachers, throughout their adolescence (MATHEIS et al, 2019). However, these effects can be moderated precisely by the family and school (MURATORI;SMITH, 2015;TWEEDALE;KRONBORG, 2015;WATTERS, 2010).…”
mentioning
confidence: 99%